Global and local rhetorics at a public-facing private company: Studiocanal and French cinema. Issue 3 (1st September 2021) - Meir, Christopher
Abstract : This article utilizes Canal+'s film production and distribution subsidiary Studiocanal as a way to understand both companies' impacts on French cinema since the formation of the subsidiary in the early 1990s. As such, the article is structured as a chronology and an analysis of the major films made in French and financed by Studiocanal in terms of their critical and popular reception. The article also examines the talent relationships underpinning this production and the trajectories of the various stars, writers, directors, and producers who worked on the films as well as the executives who oversaw them. Finally, the article analyzes the corporate rhetoric that was advanced by both Studiocanal and Canal+ over the years to position itself in the French and international markets. Synthesizing these branches of the analysis and noting certain cyclical patterns, the article argues that Studiocanal's relationship to French cinema has been complex and changeable, at times limited in favor of pursuing the international market, at times devoting ample amounts of rhetoric and resources to pursuing success in its home market. Moreover, the article demonstrates that the company's production activities have helped to mold a generation of French filmmakers and industry executives who have in turn gone on to influential careers. Looking forward, the article concludes by arguing that by virtue of its size and scale as a producer and distributor, Studiocanal will always be a significant player in French cinema.